From Idiosyncrases to Norms: An Intermediate Path - Martinez-Sierra, Juan Jose (Íkala, Revista de Lenguaje y Cultura, 2014)
The main objective of this article is to elaborate on the concept of translation tendency, understood not only as an intermediate step between a norm and an idiosyncrasy, but also as a useful tool in research focused on finding translation regularities. Given that this concept can be a source of criticism and of certain interpretations that deviate from its strict sense, this paper is intended to clarify it. Similarly, some reflections on the theory developed by Toury (1995) are included.